2019
DOI: 10.1080/08952841.2019.1593772
|View full text |Cite
|
Sign up to set email alerts
|

The night comes early for a woman”: Menopause and sexual activities among urban older Yoruba men and women in Ibadan, Nigeria

Abstract: This article explores older peoples' perceptions of menopause and sexuality in old age. The research was exploratory, consisting of 12 vignette-based focus group discussions and 18 face-to-face semistructured interviews among older Yoruba men and women (60+). Findings revealed menopause as a biopsychosocial marker of aging that provides gendered spaces for women to abstain from or suppress their sexual desires and avoid a folk pregnancy-oyun iju(folk fibroid). Older men construe menopause and sexual refusals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…It also provides some explanation why some of the women were sexually inactive when their partners were unavailable. The importance of marital relationship in predicting sexual activity among postmenopausal women has been reported in Nigeria and other countries of the world [ 26 27 28 ]. Age at menopause and duration of menopause could not significantly predict sexual activity among the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It also provides some explanation why some of the women were sexually inactive when their partners were unavailable. The importance of marital relationship in predicting sexual activity among postmenopausal women has been reported in Nigeria and other countries of the world [ 26 27 28 ]. Age at menopause and duration of menopause could not significantly predict sexual activity among the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on existing studies that specifically examined sexual activities and satisfaction among midlife men and women and the studies that paid sole attention to older men and women. 3,[18][19][20][21][22][23][24][25] However, unlike few existing studies that compared the prevalence and correlates of sexual satisfaction among the midlife and older persons. [26][27][28] This study investigated the prevalence and individual associated factors of sexual satisfaction among the midlife and older people as a distinct underserved segment of the Nigerian population.…”
Section: Discussionmentioning
confidence: 99%
“…satisfaction among midlife men and women. [17][18][19][20][21][22] Some other studies have solely focused older men and women. [23][24][25] Fewer studies in other countries have also compared the prevalence and correlates of sexual satisfaction among the midlife and older persons.…”
mentioning
confidence: 99%
“…Males abstain to protect their wives. However, some females reported that the practice promotes immorality and promiscuity among males (Agunbiade & Gilbert 2019). At times this happens openly with the husband marrying a younger wife, with the intention of relieving the menopausal wife from having sex to honour cultural beliefs as it is labelled cultural and males themselves are still sexually active.…”
Section: Taboos Idiomatic Expressions Fables Folktales and Proverbs U...mentioning
confidence: 99%